Nanoscale Brownian heating by interacting magnetic dipolar particles - Yann Chalopin (Nature Portfolio, 2017)
Abstract Clusters of magnetic nanoparticles have received considerable interest in various research fields. Their capacity to generate heat under an alternating magnetic field has recently opened the way to applications such as cancer therapy by hyperthermia. This work is an attempt to investigate the collective effects of interacting dipoles embedded in magnetic nano-particles (MNP) to predict their thermal dissipation with a liquid. We first present a general approach, based on the tracking of the microscopic dipole fluctuations, to access to the dissipation spectra of any spatial distribution of MNPs. Without any other assumption that the linear response regime, it is shown that increasing the particle concentration (dipolar interactions) dramatically diminishes and blueshifts the dissipation processes. This effect originates in a predominance of the coupling energy over the Brownian torques, which create a long-range ordering that saturates the response of the system to an external field. Consequently, the particle density is of fundamental importance to the control of the absorption of electromagnetic energy and its subsequent dissipation in the form of heat.